2016
DOI: 10.1038/srep32695
|View full text |Cite
|
Sign up to set email alerts
|

Systemic blockade of ACVR2B ligands prevents chemotherapy-induced muscle wasting by restoring muscle protein synthesis without affecting oxidative capacity or atrogenes

Abstract: Doxorubicin is a widely used and effective chemotherapy drug. However, cardiac and skeletal muscle toxicity of doxorubicin limits its use. Inhibiting myostatin/activin signalling can prevent muscle atrophy, but its effects in chemotherapy-induced muscle wasting are unknown. In the present study we investigated the effects of doxorubicin administration alone or combined with activin receptor ligand pathway blockade by soluble activin receptor IIB (sACVR2B-Fc). Doxorubicin administration decreased body mass, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
111
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(127 citation statements)
references
References 58 publications
12
111
3
1
Order By: Relevance
“…Colon 26 carcinoma (C26) cells (provided by Dr Fabio Penna, obtained from Prof. Mario P. Colombo and originally characterized by Corbett et al) were maintained in complete Dulbecco's Modified Eagle's Medium (high glucose, GlutaMAX™ Supplement, pyruvate, Gibco™, Life Technologies) supplemented with penicillin (100 U/mL), streptomycin (100 μg/mL), and 10% FBS. Our pilot experiments showed that injecting mice with C26 cells (5 × 10 5 ), resulted in marked cachexia and considerably higher tumour gene expression of Activin A , Interleukin ‐ 6 ( Il ‐ 6 ) and Myostatin in comparison to our previously conducted experiment using the LLC tumour model ( Online Resource 1: Figure S1) with the same number of cells injected (5 × 10 5 ), but larger tumour (data not shown).…”
Section: Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…Colon 26 carcinoma (C26) cells (provided by Dr Fabio Penna, obtained from Prof. Mario P. Colombo and originally characterized by Corbett et al) were maintained in complete Dulbecco's Modified Eagle's Medium (high glucose, GlutaMAX™ Supplement, pyruvate, Gibco™, Life Technologies) supplemented with penicillin (100 U/mL), streptomycin (100 μg/mL), and 10% FBS. Our pilot experiments showed that injecting mice with C26 cells (5 × 10 5 ), resulted in marked cachexia and considerably higher tumour gene expression of Activin A , Interleukin ‐ 6 ( Il ‐ 6 ) and Myostatin in comparison to our previously conducted experiment using the LLC tumour model ( Online Resource 1: Figure S1) with the same number of cells injected (5 × 10 5 ), but larger tumour (data not shown).…”
Section: Methodsmentioning
confidence: 63%
“…Muscle protein synthesis was analysed using surface sensing of translation method as earlier in our laboratory . Briefly, on Day 11 after C26 cell inoculation, mice were anaesthetized and subsequently injected i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a soluble activin type IIA-receptor has been shown to increase bone mass in several in vivo [5, 6, 8] models. The effects of soluble activin type IIB-receptor (ActRIIB-Fc) on bone metabolism have also been studied recently [912]. Furthermore, exercise, in addition to its various other health benefits, may have positive effects on bones of young individuals [13, 14].…”
Section: Introductionmentioning
confidence: 99%